Pemanfaatan Limbah Teh, Sekam Padi, Dan Arang Sekam Sebagai Media Tumbuh Bibit Trembesi (Samanea Saman) - Sudarsono Efendi Sofyan; Melya Riniarti; Duryat Duryat (Jurnal Sylva Lestari, 2014)
Rain Tree (Samanea saman) has ability to absorb the carbon dioxide from the air. Due to it's advantages, there was a need to know the propagation way. Using organic materials such as tea waste, rice husk and husk charcoal as a growing medium  diggested could increase the seedling growth. This study aims to: (1) determined the effect of tea waste, rice husk and husk charcoal as a growth media for rain tree seedling (2) determined the best composition of the media among soil mixture with tea waste, soil with mixture rice husk and soil with mixture husk charcoal. The research was conducted from September 2012 to December 2012, in the greenhouse, Faculty ofÂ  Agriculture, University of Lampung. The study was designed in completely randomized design (CRD) used 7 treatment with 5 replications, each consisted of 5 sample. Treatment consists of: 100% soil, soil + tea waste (75% + 25%), soil + tea waste (50% + 50%), soil + rice husk (75% + 25%), soil + rice husk (50% + 50%), soil + husk charcoal (75% + 25%), soil + husk charcoal (50% + 50%). Provision of tea waste, rice husk and husk charcoal was gave effect on canopy dry weight, stem dry weight, roor length, seed quality indexÂ  and did not give affect on height and diameter of seedling, the appropriate composite media for each type of mixture was a composite soil + tea waste (75% + 25%), soil + rice husk (50% + 50%), of the soil + husk charcoal (75% + 25%). Keywords: organic material, rain tree , tea waste, waste, husk charcoal